Ethics in cyberspace: civil and shariah perspective - Mohamed, Duryana (2008)
Ethics and morality is debatable. But the concept of ethics always relate to moral responsibilities.It is debatable due to different views and different interpretation on what is considered as unethical and immoral conduct. Sometimes certain acts are not unethical or immoral in certain countries but considered as immoral in the other country. Basically, the word ‘Ethics’ is derived from the Greek word ethikos, which means a system of rules of behaviour. In modern usage it means the science of morals.